Hubungan Antara Dukungan Sosial Dengan Minat Berwirausaha Pada Mahasiswa Fakultas Psikologi Untag Surabaya (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2020)
Improving the economy of a country can be increased by at least 4% of its people to become entrepreneurs. However, entrepreneurial interest is not easy to increase because Indonesian people who apply the principle that being an employee is highly respected rather than entrepreneurial. Entrepreneurial interest can be enhanced by the existence of individual self-will and support from the environment. Entrepreneurial interest is defined as a psychological aspect that supports individuals to carry out or carry out their duties properly in accordance with their wishes. The purpose of this study is to find out and obtain data related to the relationship between social support with entrepreneurial interest in students. The number of samples of this study were 125 people. This research is a correlational quantitative study that compares the relationship between social support and entrepreneurial interest in students and uses the product moment statistical analysis test. The results show that there is a very significant positive correlation with the rxy score of 0.681 with a p value of 0.000 (p <0.01), which means it is very significant. The effective contribution in this 46% which means that social support is proven to influence entrepreneurial interest. While 54% of entrepreneurial interest is influenced by other factors. Keywords: social support, entrepreneurship interests, students